Syntheses and Crystal Structures of a Novel 20‐Membered N3O2 ‐Donor Macrocycle and Its Disilver(I) Bis(Macrocycle) and Monocadmium(II) Complexes. (30th September 2015) - Kang, Dong Hee; Choi, Kyu Seong
Abstract :